2021
DOI: 10.1002/cssc.202100001
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversion of Biomass to Furanic Derivatives with Deep Eutectic Solvents

Abstract: Biomass is the only renewable organic carbon resource in nature, and the transformation of abundant biomass into various chemicals has received immense spotlight. As a novel generation of designer solvents, deep eutectic solvents (DESs) have been widely used in biorefinery due to their excellent properties including low cost, easy preparation, and biodegradability. Although there have been some reports summarizing the performance of DESs for the transformation of biomass into various chemicals, few Reviews ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 130 publications
1
26
1
Order By: Relevance
“…over ionic liquids [37]. Many researchers reported that DESs can act as reaction mediums and provide Brønsted acidity to convert biomass into furfural [38]. Choline chloride-oxalic acid-based DESs were used as a solvent and a catalyst to produce furfural with a 26.3% yield from oil palm fronds at 100 • C for 135 min [39].…”
Section: Homogeneous Catalysts For the Furfural Productionmentioning
confidence: 99%
“…over ionic liquids [37]. Many researchers reported that DESs can act as reaction mediums and provide Brønsted acidity to convert biomass into furfural [38]. Choline chloride-oxalic acid-based DESs were used as a solvent and a catalyst to produce furfural with a 26.3% yield from oil palm fronds at 100 • C for 135 min [39].…”
Section: Homogeneous Catalysts For the Furfural Productionmentioning
confidence: 99%
“…With growing concerns over energy reserves and climate change, utilization of renewable lignocellulosic biomass to produce high value-added chemicals and liquid biofuels is considered a promising alternative route not only to reduce over-dependence on fossil resources but also to meet with the development of economy and society. [1][2][3][4][5][6] Lignocellulosic biomass consists of three main components: 30-50% of cellulose, 20-35% of hemicellulose, and 15-30% of lignin. Among them, lignin with aromatic monomers in its structure is the only scalable renewable feedstock which can be converted to valuable aromatic chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…From the different chemicals that can be obtained from renewable resources, furfural is among the most relevant, with a world market of around 300,000 tons per year, while being identified by the US Department of Energy (DOE) as one of the top 12 value-added chemicals attained from biomass [ 4 ]. This compound is a precursor of other essential chemicals that are intermediates and/or solvents in industry, such as 2-methyltetrahydrofuran (2-Me-THF), furan, tetrahydrofuran (THF) and 2-methylfuran [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…These issues are mainly attributed to the nature of the catalysts. Acidic catalysts can cause the formation of side products such as humins, resulting from furfural condensation, while heterogeneous catalysts display low accessibility to biomass [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation